On Metaphorical Exemplification in Music: A Reply to Sousa - Guerreiro, Vitor (Res Facta Nova, 2025)
I address a series of difficulties raised by Tiago Sousa against the use of Nelson Goodman's concept of metaphorical exemplification to explain expressiveness in music, especially purely instrumental music. My aim is not exactly to defend Goodman, but rather the soundness or plausibility of using metaphorical exemplification in explaining expressiveness. I approach Sousa’s difficulties in two blocs: i) his first and third problems challenge the metaphorical character of certain descriptions of music, and the consistency of metaphorical (as opposed to literal) exemplification; ii) his second problem is directed at the compatibility between exemplification (metaphorical or otherwise) and expressiveness. I focus especially on this second problem: if what a musical work expresses is uniquely bound to the experience of that musical work and no other, how can expressiveness be anything like the exemplification of properties by samples? My further aim, more than dispelling these difficulties beyond any doubt, is to rekindle discussion of Goodman’s ideas on expressiveness. They are just too fashionably out of fashion, which is always a sign that some stirring is in order.